Perspectives de gouvernance environnementale durable dans la région de Lwiro (Sud Kivu, République Démocratique du Congo) - Innocent Karhagomba Balagizi; Serge Ngendakumana; Hermes Namegabe Mushayuma; Trésor Mirindi Adhama; Alphonse Muhimuzi Bisusa; Bajope Baluku; Mwapu Isumbish (VertigO)
This chapter describes the environmental assessment process of Lwiro region identified among the major agricultural area of the province of South-Kivu. This site shows a larger agro-ecosystem complex and is located between Kahuzi-Biega national park (protected area) and Lake Kivu (aquatic ecosystem). It hosts a poor and dense rural population. This study aims to create an integrated community-based conservation approach with a look on poverty alleviation and food security. The chapter describes also the environmental perceptions of rural population in plagued with the "modern" civilization. Environmental assessment parameters are defined such as soil and water quality, occurrence of zoonoses, famine period characteristics and management, human pressures on natural resources, forest management… The existence of a community-based conservation committee seems to be a driving rehabilitation or environmental conservation.